UMPSA students uphold traditional Malay dance in Islamabad, Pakistan - Noor Afiza, Mohd Asmi (UMPSA, 2024)
ISLAMABAD, 12 September 2024 – Four students of Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) were invited to Islamabad, Pakistan, in conjunction with the 67th Independence Day celebration and the Malaysian Food Festival organised by the High Commission of Malaysia in collaboration with the Serena Hotel, Islamabad on 3 to 12 September 2024.